Pengembangan Media Puzzle Berbasis Kearifan Lokal Kediri untuk Meningkatkan Hasil Belajar Materi Membandingkan Jenis-Jenis Segitiga Kelas V SDN Mrican 2 - Yuana Ayu Azhari; Aan Nurfahrudianto; Jatmiko (Lembaga Yasin AlSys, 2026)
Although learning media have been widely developed in previous studies, research specifically addressing the development of puzzle-based learning media incorporating Kediri local wisdom for comparing types of triangles in elementary schools remains limited. This study aimed to analyse the validity, practicality, and effectiveness of puzzle-based learning media incorporating Kediri local wisdom in improving the learning outcomes of fifth-grade students at SDN Mrican 2 on the topic of comparing types of triangles. This study employed a quantitative approach with a research and development (Research and Development) design using the 4D model, which comprises the define, design, develop, and disseminate stages. The research participants consisted of material expert validators, media experts, a fifth-grade teacher, and fifth-grade students at SDN Mrican 2. Data were collected through interviews, validation questionnaires, teacher and student response questionnaires, and pretest and posttest assessments. The data were analysed using quantitative descriptive analysis techniques and N-Gain calculations. The results showed that the developed media achieved a very high level of validity, with validation percentages of 96% from the material experts and 86% from the media experts. The practicality of the media was also classified as very high, based on a teacher response of 96% and a student response of 92%. The effectiveness of the media based on the N-Gain test reached 57.04% in the limited trial and 66.39% in the large-scale trial, both of which were classified as moderate. These findings indicate that puzzle-based learning media incorporating Kediri local wisdom can improve students’ learning outcomes on the topic of comparing types of triangles. Thus, the developed media were declared valid, practical, and moderately effective for use in elementary school mathematics instruction. This study provides a practical contribution for teachers by providing innovative, contextual, and engaging learning media while strengthening the development of learning media based on local wisdom. Further studies may develop similar media for other mathematics topics or different levels of education.